PENERAPAN MODEL SAVI (SOMATIC, AUDITORY, VISUAL, INTELLECTUAL) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN ION DAN pH LARUTAN PENYANGGA DI KELAS X MIPA SMA NEGERI 2 PEKANBARU - Sahmiati Boangmanalu; Betty Holiwarni; Jimmi Copriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research has been conducted at SMAN 2 Pekanbaru which aims to improve student learning outcomes on the subject of equilibrium ions and pH buffer solutions in class XI MIPA. This type of research is an experimental study with a design Randomized Control Group pretest-posttest.. The sample from the study was students of class XI MIPA 2 as an experimental class. The experimental class is the class applied to the SAVI model. The data analysis technique used is the t-test. Based on the results of the data analysis test, t count> t table is 4,296 > 1.67, with category of improving learning outcomes is 0,79 which is a high category.It can be concluded that the application of SAVI Model can improve student learning outcomes in the points of equilibrium ions and pH buffer solution in the class X MIPA of 2 Pekanbaru State High School with category of improving learning outcomes is 0,79 which is a high category.Key Words: Learning, Learning outcomes, equilibrium ions and pH buffer solution